Correlation of E-cadherin Immunoexpression with Histopathological Grading of Oral Squamous Cell Carcinoma - Khaliduzzaman, F M; Hye, A Q M Abdul; Mimi, Shamim Akhter; Pew, Nibedita Das; Hasem, Abu Saeed Bin; Faroque, Abdullah Al; Karim, Syeda Noorjahan; Rahman, Tasnim (Mediscope, 2025)
Background: Cancers arising from the oral cavity are mostly squamous cell carcinoma. E-cadherin is encoded by the CDH1 gene that helps in maintaining cell polarity and normal tissue architecture. Loss of E-cadherin expression is associated with tumor differentiation, invasion, metastasis and poor prognosis. Objectives: To assess the E-cadherin expression in different grades of oral squamous cell carcinoma (OSCC) and to determine the association of E-cadherin expression with histological grades, age & gender of OSCC patients. Methods: This cross-sectional observational study was conducted at the Department of Pathology, Sylhet MAG Osmani Medical College, from July 2021 to June 2022. A total of 53 (small biopsy and resected) OSCC cases were processed; paraffin blocks were made and stained with routine H&E stain. The sections were examined microscopically and the tumors were graded histologically. Immunohistochemistry was performed by using a commercially available anti-E-cadherin antibody. Immunoreactivity was calculated by multiplying the expression score and the intensity score. Results: Out of 53 cases of OSCC, most of the cases (35/53) were found in the buccal mucosa (66.0%) followed by in the tongue (18.9%). 50.9% of patients belonged to Grade-I, 43.4% were Grade-II and 5.7% were Grade-III OSCC. Regarding E-cadherin, 56.6% of cases showed positive expression, 39.6% cases showed reduced expression and 3.8% cases showed negative expression. Negative expression was found only in 2 (66.7%) Grade III cases of OSCC. A significant correlation was seen between E-cadherin expression with histological grading but not with age and gender. Conclusion: E-cadherin might be a valuable tool for predicting OSCC patient outcomes and it can be further used for therapeutic targets. Mediscope 2025;12(1): 23-28